2013
DOI: 10.18388/abp.2013_2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti-apoptotic pathways activated by BCR/ABL in the resistance of chronic myeloid leukemia cells to tyrosine kinase inhibitors.

Abstract: Chronic myeloid leukemia (CML) is a hematological stem cell disorder characterized by the excessive proliferation of the myeloid lineage. In its initial chronic phase, the myeloid progenitor cells expand and demonstrate apparently normal differentiation. The disease may then transform into the accelerated phase, usually associated with resistance to therapy, and finally, into acute leukemic progression phase - blast crisis. Abnormal myeloid cells produce progenitors, which have lost their ability to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 147 publications
(141 reference statements)
0
14
0
Order By: Relevance
“…AND THE JAK2/STAT3/5 SIGNALING PATHWAY CML is characterized by the overexpression of the Bcr/Abl gene, which plays a crucial role in the resistance of CML cells to apoptosis [Danisz and Blasiak, 2013]. It has been reported that Bcr/Abl-JAK/STATs activity in CML was associated with the inhibition of differentiation, apoptosis, cell cycle progression, and oncogenic signaling pathways.…”
Section: Dehydrocostus Lactone Inhibited the Expression Of Bcr/ablmentioning
confidence: 99%
“…AND THE JAK2/STAT3/5 SIGNALING PATHWAY CML is characterized by the overexpression of the Bcr/Abl gene, which plays a crucial role in the resistance of CML cells to apoptosis [Danisz and Blasiak, 2013]. It has been reported that Bcr/Abl-JAK/STATs activity in CML was associated with the inhibition of differentiation, apoptosis, cell cycle progression, and oncogenic signaling pathways.…”
Section: Dehydrocostus Lactone Inhibited the Expression Of Bcr/ablmentioning
confidence: 99%
“…Chronic myeloid leukemia (CML) is a myeloproliferative disorder characterized by the BCR-ABL gene rearrangement (1,2). As a driving force for leukemogenesis of CML, the activated tyrosine kinase of BCR-ABL stimulates multiple signaling pathways that confers growth advantage and counteracts apoptosis (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have found that BCR/ABL was involved in many signaling pathways, including the PI3K/AKT, Ras and JAK/STAT signaling pathways, which are activated by BCR/ABL, resulting in malignant proliferation of CML cells. These pathways are also involved in the resistance to apoptosis in CML cells and are associated with imatinib resistance in CML patients (Danisz & Blasiak, ). Pathway enrichment involves cytokine‐cytokine receptor pathways, including tyrosine kinase receptor activity and phosphokinase receptor and androgen receptor pathway activation; TKIs are currently the primary treatment for CML patients (Arrigoni et al, ).…”
Section: Discussionmentioning
confidence: 99%